Missing appointments by patients on antiretroviral therapy: Professional nurses' perspective - Mygirl P. Lowane; Rachel T. Lebese (AOSIS, 2022)
Background: Missed appointments for medicine pick-ups are regarded as a predictor of poor adherence, and should trigger immediate questions about issues that may affect follow-up visits to healthcare settings. Objectives: The study explored and described professional nurses' perspectives about the factors that contribute to missing appointments by people living with Human Immunodeficiency Virus (PLWHIV) on antiretroviral therapy (ART) at Mopani and Vhembe district in Limpopo Province. Method: A qualitative explorative contextual approach was used for the study. Non-probability, purposive sampling was used to select 14 professional nurses who met the inclusion criteria. Data were collected through face-to-face unstructured interviews. One central question was asked and probing questions were based on the participants' responses to the central question. Thematic analysis of the findings was carried out. Trustworthiness was ensured through intercoder agreement, audio recording, triangulation, bracketing, and member checking. Required permission, approval, and ethical clearance were also ensured. Results: Organisational health system and management of the healthcare facility were found to be the barriers that negatively impacted on the ability of the PLWHIV on ART to maintain clinic visits appointments. Lack of patient involvement, stereotyped appointment dates selection, poor patient-provider relationships, errors of recording appointment dates and long waiting times came up as sub-themes derived from the main theme. Conclusion: The results suggest that there is a need to increase and improve mutual trust in patient-provider relationships, improve nurses working conditions, develop proper booking systems and reduce clinic waiting hours.